Telehealth during and beyond the COVID-19 Pandemic: Evidence from licensed dietitians in an emerging economy - Maya Assaad; Nour Chamma; Miroslav Mateev; Rana Rizk (PLoS ONE, 2026)
Background The sudden onset of the SARS-Cov-2 (COVID-19) pandemic disrupted access to in-person nutrition consultation and prompted the rapid adoption of telehealth by dietitians. Objective This study investigates the use of telehealth among Lebanese Licensed Dietitians (LDs) during COVID-19, in the absence of national telehealth practical guidelines (TPG), and offers insights into its application amid overlapping crises including a pandemic, economic crisis, and infrastructure disruption in Lebanon. Design A cross-sectional study conducted in March 2023, using an anonymous 44-question online survey, distributed via the Lebanese Order of Dietitians and social media platforms. Participants: Ninety-four dietitians participated (98.9% female, mean(SD) age: 30.54(6.41) years); mean(SD) experience: 7.89(5.7) years). Most reported practicing clinical nutrition as their primary practice area (87.2%), primarily in weight management (84%). Main outcome: Measures included Dietitians’ experience with telehealth, tools used in remote consultations, perceived barriers and facilitators, and perspectives on future application. Statistical analyses: Descriptive analysis (counts, frequencies) were analyzed using SPSS version 28. Results Telehealth use rose from 48.4% before COVID-19 to 97.8% during it. Commonly used platforms included WhatsApp (90.3%), Zoom (72.0%), and e-mails (41.9%). Reported barriers included bad internet connection (74.2%), patients preferring face-to-face consultation (61.3%), and patients unfamiliar with emerging videoconferencing technologies (33.3%). Benefits included scheduling and time flexibility (83.9%), decrease in practice-related costs (77.4%), and compliance with social distancing measures (53.8%). Most respondents acknowledged that Telehealth is needed (78.5%) and applicable in the Lebanese context (64.6%) and called for telehealth trainings (78.5%) and national TPG development (74.2%). Conclusion This study recognizes the growing use of telehealth in Lebanon, underscoring the need for telehealth with national regulations and evidence-based guidelines. Despite limited infrastructure, LDs continued delivering care, emphasizing the urgency for secure and standardized frameworks to support ethical and sustainable digital health practice.